UPAYA MENINGKATKAN ASPEK AFEKTIF SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MENGGUNAKAN METODE GAME BASED LEARNING KEPADA SISWA KELAS V SDN 3 POHGADING TIMUR - Salihin; Susi Yundarwati; Fadli Zaenuddin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The problem faced bay sports educators in delivring material and practices in physical education learning is that learning abaut sport is not enjoyable, making students feel bored and lazy in exercising, therefore researchers are interesed in conducting researcah on students at SDN 3 east pohgading timur, especially for classes v. The aim to be achieved in this research is to increase students’ affective aspects in learning physical education, sport and health using game based learning methods for class students at SDN 3 pohgading timur. The research method used is the calssroom action research (PTK) model which wil be implemented using the game based learning method. The population and sample used were 18 class V students. The instrumen used was an abservation sheet for increasing affective aspects in cycle one and cycle two, then continued with data analysis using an observation sheep for assessing students’ affective aspects. The results of the research showed that it was proven that in the two cycle meetings, students' affective aspects in learning physical education, sports and health using the game based learning method were able to increase, in the first cycle they got 40% points, while in the second cycle meeting they got 80% points, which is a